2015
DOI: 10.1371/journal.pntd.0003900
|View full text |Cite
|
Sign up to set email alerts
|

Functional Activity Limitation and Quality of Life of Leprosy Cases in an Endemic Area in Northeastern Brazil

Abstract: BackgroundFew studies have evaluated the association between quality of life (QoL) and functional activity limitations (FAL) of leprosy patients as determined by the Screening of Activity Limitation and Safety Awareness scale (SALSA).AimTo identify the association between FALs and the QoL of patients during and post leprosy treatment.Materials and MethodsCross-sectional survey of 104 patients with leprosy followed in specialist reference centres in Sergipe, Brazil, between June and October 2014. QoL was evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
58
1
13

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(81 citation statements)
references
References 15 publications
7
58
1
13
Order By: Relevance
“…Reaction symptoms are more severe and incapacitating in MB, as indicated by the development of ulcers and blisters, presence of edema, and reports of pain and fever . Santos and colleagues showed that 75% of the patients reported pain, classified as moderate intensity in 43.1% and severe intensity in 48.2% of the cases. Moreover, pain was associated with the presence of leprosy reactions, as disabilities and lower quality of life .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reaction symptoms are more severe and incapacitating in MB, as indicated by the development of ulcers and blisters, presence of edema, and reports of pain and fever . Santos and colleagues showed that 75% of the patients reported pain, classified as moderate intensity in 43.1% and severe intensity in 48.2% of the cases. Moreover, pain was associated with the presence of leprosy reactions, as disabilities and lower quality of life .…”
Section: Discussionmentioning
confidence: 99%
“…Santos and colleagues showed that 75% of the patients reported pain, classified as moderate intensity in 43.1% and severe intensity in 48.2% of the cases. Moreover, pain was associated with the presence of leprosy reactions, as disabilities and lower quality of life . We found an association between the MB group and presence of reactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Penelitian tentang kualitas hidup penderita kusta yang dilakukan oleh Manker, J. M., Sumedha, J. M., Deepa, V. H. & Mhatre (2011) menunjukkan bahwa skor kualitas hidup penderita kusta lebih rendah dibandingkan kualitas hidup bukan penderita kusta. Faktorfaktor yang mempengaruhi kualitas hidup penderita kusta antara lain jenis kusta yang diderita (An 2009) derajat kecacatan akibat kusta, distres psikologis dan keterbatasan aktivitas akibat komplikasi kusta (Santos 2015) kondisi tempat tinggal dan adanya isolasi dari lingkungan serta adanya stigma yang dialami oleh penderita (Rahayunuingsih 2012).…”
Section: Pendahuluanunclassified
“…Penderita kusta yang memiliki persepsi keseriusan positif, maka akan berusaha mencari pengobatan guna mencegah terjadinya kecacatan dan kematian, karena kecacatan merupakan salah satu faktor yang dapat mempengaruhi kualitas hidup penderita kusta. Santos (2015) menyatakan bahwa keterbatasan aktivitas fisik memiliki hubungan dengan kualitas hidup penderita kusta khususnya dalam domain kesehatan fisik dan lingkungan.…”
Section: Hubungan Persepsi Individu: Persepsi Keseriusan Dengan Kualiunclassified